2020
DOI: 10.1111/trf.15720
|View full text |Cite
|
Sign up to set email alerts
|

Ferroportin inhibition attenuates plasma iron, oxidant stress, and renal injury following red blood cell transfusion in guinea pigs

Abstract: BACKGROUND Red blood cell (RBC) transfusions result in the sequestration and metabolism of storage‐damaged RBCs within the spleen and liver. These events are followed by increased plasma iron concentrations that can contribute to oxidant stress and cellular injury. We hypothesized that administration of a ferroportin inhibitor (FPN‐INH) immediately after acute RBC exchange transfusion could attenuate posttransfusion circulatory compartment iron exposure, by retaining iron in spleen and hepatic macrophages. STU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Repeated blood transfusions had no effects on iron concentrations in liver or heart, but increased kidney iron levels in Hbb th3/+ mice, likely due to iron derived from transfused RBC. 11 In transfused or non-transfused Hbb th3/+ mice, vamifeport had no significant effects compared with vehicle treatment on liver and heart iron content, suggesting that vamifeport does not remove existing iron, but rather prevents further iron accumulation in cells from these tissues. 1 In contrast, vamifeport significantly reduced spleen iron content in non-transfused Hbb th3/+ mice ( Online Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Repeated blood transfusions had no effects on iron concentrations in liver or heart, but increased kidney iron levels in Hbb th3/+ mice, likely due to iron derived from transfused RBC. 11 In transfused or non-transfused Hbb th3/+ mice, vamifeport had no significant effects compared with vehicle treatment on liver and heart iron content, suggesting that vamifeport does not remove existing iron, but rather prevents further iron accumulation in cells from these tissues. 1 In contrast, vamifeport significantly reduced spleen iron content in non-transfused Hbb th3/+ mice ( Online Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 92%
“… 10 Moreover, these patients often show elevated transferrin saturation (TSAT) and non-transferrin-bound iron (NTBI), triggered by ferroportin-mediated iron release from macrophage recycling of damaged RBC, which can lead to oxidative stress, vascular injury and organ iron overload. 8 , 11 In addition, the accelerated recycling of RBC due to blood transfusions results in a high serum iron concentration and an increase in NTBI that correlates with the occurrence of heart disease. 12 …”
Section: Introductionmentioning
confidence: 99%
“…To better clarify the extent of the change in kidney function, additional experiments will be necessary to assess renal function after 48 h. Acute kidney injury (AKI) after RBC transfusion is usually associated with excess iron in the circulation and if ferritin is not present to remove the excess of iron, it can cause even worse clinical outcomes. Baek et al demonstrated that administration of a ferroportin inhibitor to switch compartmentalization of iron from the plasma to the spleen and liver, prevents post-transfusion iron accumulation, oxidative stress, and AKI 42 . Unlike the published study, we elected to use whole blood instead of RBCs, but we believe that potential iron toxicity still remains as mechanism of iron toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Baek et al . demonstrated that administration of a ferroportin inhibitor to switch compartmentalization of iron from the plasma to the spleen and liver, prevents post-transfusion iron accumulation, oxidative stress, and AKI 42 . Unlike the published study, we elected to use whole blood instead of RBCs, but we believe that potential iron toxicity still remains as mechanism of iron toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Iron overload can occur in patients with inherited diseases, such as hereditary haemochromatosis [ 3 ] and β thalassaemia [ 4 ], or secondary to iron overload during blood transfusion and haemolysis [ 5 ]. Iron accumulation in multiple organs causes extra clinical problems and oxidative damage in the liver [ 6 ], pancreas [ 7 ] and kidney [ 8 ]. The metabolism of non-transferrin-bound iron results in reactive oxygen species, which are linked to apoptosis, necrosis, and cellular malfunction [ 9 ].…”
Section: Introductionmentioning
confidence: 99%